2021
DOI: 10.1177/21582440211059180
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Leisure Tourism: From the Perspective of Tourist Touch Points and Perceived Well-being

Abstract: The current study empirically examines an integrative model linking multiple types of touch points in tourism experience, hedonic well-being, eudaimonic well-being, revisit intention, and online word of mouth, in response to the calls to revitalize tourism and achieve sustainable development. The research relied on “Nong Jia Le,” an important representative survey on leisure tourism. The questionnaire was developed based on prior studies, then translated into Chinese and set up in an online survey system. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…Currently, social media plays a crucial role in bridging the consumer experience gained from word-of-mouth. This result accords with Chen et al (2021) finding that when tourists perceive high levels of pleasantness or relaxation, they are more likely to provide positive word-of-mouth for that destination on social media. The finding suggests that availability of relaxation, and learn local culture from destination willing to motivate the tourist to generate a good e-WoM.…”
Section: Testing the Mediation Effectsupporting
confidence: 89%
“…Currently, social media plays a crucial role in bridging the consumer experience gained from word-of-mouth. This result accords with Chen et al (2021) finding that when tourists perceive high levels of pleasantness or relaxation, they are more likely to provide positive word-of-mouth for that destination on social media. The finding suggests that availability of relaxation, and learn local culture from destination willing to motivate the tourist to generate a good e-WoM.…”
Section: Testing the Mediation Effectsupporting
confidence: 89%
“…Touch evaluation frequently emphasizes surface characteristics and subjective experiences. Touch influences preferences, health, and product satisfaction [ 26 ]. Many studies have been conducted to evaluate how material surface sensory characteristics affect emotional touch assessment [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other research carried out by Wearing and Foley (2017) has evaluated tourists' experiences in the context of cities and Chhetri et al (2004) in the context of nature-based destinations. The study of Backman et al (2022) showed that the restorative environment is an essential aspect of the wellness experience, contributing to positive emotions and life satisfaction and determining an individual's loyalty and intention to revisit; moreover, the findings of the investigation of Chen et al (2021) found that both hedonic and eudaimonic well-being significantly affect consumers' intention to revisit the destination and to spread word of mouth online.…”
Section: Introductionmentioning
confidence: 99%